Phase-adjustment of human circadian rhythms by light and physical exercise - Yamanaka, Y.; Waterhouse, J. (The Journal of Physical Fitness and Sports Medicine, 2016)
The human circadian system derives from two distinct circadian oscillators that separately regulate circadian rhythms of body temperature and plasma melatonin, and of the sleep-wake cycle. The oscillator for body temperature and melatonin is the central circadian pacemaker, located in the hypothalamic suprachiasmatic nucleus (SCN), and the oscillator for sleep-wake cycle is another oscillator, located in the brain but outside the SCN. Although bright light is a primary zeitgeber for circadian rhythms, non-photic time cues such as a strict sleep schedule and timed physical exercise act as a non-photic zeitgeber for the sleep-wake cycle under dim light conditions, independent on the SCN circadian pacemaker. Recently, timed physical exercise under bright light has been shown to accelerate re-entrainment of circadian rhythms to an advanced sleep schedule. Physical exercise may enhance the phase-shift of circadian rhythm caused by bright light by changing light perception. In the field of sports medicine and exercise science, adjustment of the circadian rhythm is important to enable elite athletes to take a good sleep and enhance exercise performance, especially after inter-continental travel and jet lag.